Modifications of membrane phospholipids in response to extended aging in pork loins - Donaldson, Elizabeth; Wu, Wan Jun; Chao, Michael (My University, 2019)
Meat quality deterioration during the aging process could be partially caused by phospholipid oxidation. Therefore, the objective of the study was to evaluate modifications of phospholipids in three different aging periods. In this study, Duroc sired crossbred pigs were processed at a commercial harvest facility in the Midwest. Loins from 20 carcasses were collected at one-day postmortem. Three chops containing the longissimus muscle were vacuum packaged and aged at 4 degree C. The three chops were aged for either 1, 8 or 21 days. The lipid was extracted from each sample using the Folch method and prepared for lipidomic analysis. The samples were taken to K-State Lipidomics Research Center where mass spectrophotometry was used to analyze phospholipid species (n=60). Total phospholipid quantity remained the same from day 1 to day 8 (P>.05). However, total phospholipid quantity decreased significantly from day 8 to day 21 (P<.05). All classes of phospholipid quantity decreased from aging 1 to 21 days (P<.05). There were significant changes in the molar percentage in three phospholipid classes: lysophosphatidylethanolamine (LPE), phosphatidylinositol (PI), and phosphatidylserine (PS). LPE molar percentage decreased significantly from day 8 to 21 (P<.05). PI and PS molar percentage increased significantly from day 1 to 21 (P<.05). The results indicated that PI and PS are more resistant to degradation in comparison to other phospholipid classes. In conclusion, our results confirm that phospholipids experience significant degradation throughout the aging process. Certain phospholipid classes like PI and PS are more resistant to degradation compared to other classes. More research on alterations of phospholipids during aging will help to shed light on shelf-life extension in pork.
Keywords: Spring 2019